2017
DOI: 10.4028/www.scientific.net/kem.738.15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Natural Frequencies of Voided Biaxial Concrete Slabs

Abstract: Voided slabs using voids formed by permanent fillers or removable forms have been used in reinforced concrete floor systems for more than 100 years. In this article we will focus on the natural frequency of voided biaxial slabs system Cobiax. Cobiax void former modules are synthetic hollow spheres or rotational ellipsoids mounted in the relevant spaces between the upper and lower reinforcement. We have analyzed the slabs of different thicknesses with adequate void former modules and spans following the manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In the past, the vibrations were mainly eliminated by robustness of the slabs, stemming from the need to factor in inaccuracies of calculations at given time. This robustness granted grater stiffness therefore higher natural frequencies [6]. Currently, floor slabs are becoming more and more subtle, as all load-bearing elements are generally being designed to be used to their limit thanks to finite element method (FEM), that is allowing for highly precise calculations.…”
Section: Floor Vibrationssources Problems Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, the vibrations were mainly eliminated by robustness of the slabs, stemming from the need to factor in inaccuracies of calculations at given time. This robustness granted grater stiffness therefore higher natural frequencies [6]. Currently, floor slabs are becoming more and more subtle, as all load-bearing elements are generally being designed to be used to their limit thanks to finite element method (FEM), that is allowing for highly precise calculations.…”
Section: Floor Vibrationssources Problems Solutionsmentioning
confidence: 99%
“…Their weight may decrease by as much as 40% [5]. Other advantages of such slabs are their ability to span larger spans [6], their reduced thickness that allows for lower floor-to-floor height. In addition their lower weight is beneficial in seismic design, as seismic loads induced by movement of lighter slabs are smaller [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Research has also been carried out in studying the natural frequencies as well as behavior of voided slabs as a function of length. 17,18 Evaluation of vibration response for steel framed floor systems have been done in meeting the serviceability limits. 19,20 Weckendorf et al 21 also studied the floor vibration response of wood light weight buildings and concluded that architectural and construction detailing decisions play a major role in determining whether or not a particular building is likely to exhibit floor vibration serviceability problems.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive tests have been done on a composite floor system to measure various vibration characteristics like the fundamental frequency and damping ratio as well as to determine effects of modal damping ratio on peak acceleration 13–16 . Research has also been carried out in studying the natural frequencies as well as behavior of voided slabs as a function of length 17,18 . Evaluation of vibration response for steel framed floor systems have been done in meeting the serviceability limits 19,20 .…”
Section: Introductionmentioning
confidence: 99%